The investigation of the mechanical properties of MAX phase and cubic boron nitride ceramic composite made by spark plasma sintering - Rampai, Tokoloho (My University, 2021)
The MAX Phases, which are unique new carbide and nitride ternary ceramics, have the main advantages of both metals and ceramics: they are generally soft, machinable, heat-tolerant, strong and lightweight. Composites of MAX phases and Cubic boron nitride (cBN) could have a wide array of applications. The problem in making these composites lies in the reactivity of MAX phases and cBN. The cBN abrasive proportions used were 20 and 40 vol.%, and the average cBN particle sizes used were 10 and 100 μm cBN. Using the SPS method, the pressure was kept constant at 30 MPa throughout and temperatures varied from 700 to 1600°C. Successful samples in this study were defined as those that displayed abundant MAX phase and cBN in the sample, with minimum to no hBN presence. The reactivity of the Ti2AlC, Ti3AlC2 and Ti3SiC2MAX phases with the cBN was determined to be the simultaneous hexagonalisation of cBN and reaction of the resultant hBN with the MAX phases. The resultant secondary phases were; hBN (in some cases), AlN/TiaAlb, TiB2 and TiCxNy (and/or TiC and TiN)from the Al based MAX phase composites. The phases present were hBN (in some cases), SiC, TiB2and TiCxNy (and/or TiC and TiN) from the Ti3SiC2 composites. It was observed that decreasing the surface area and/or increasing the volume fraction of the cBN had a stabilising effect on the MAX phase formation in the composites. The optimum conditions for synthesising Ti2AlC based composites were 1250°C for 5 minutes for all sizes and fractions of cBN. For the Ti3AlC2 based composites, the optimum conditions were 1300°C for 10 minutes, for the 20 vol.% cBN composites, and 1350°C for 5 minutes for the 40 vol.% cBN composites. For the Ti3SiC2 based composites, the optimum conditions were 1250°C for 5 minutes for the 20 vol.% composites and 1300°C for 5 minutes for the 40 vol.% cBN composites. The SEM analysis of selected samples showed the cBN and MAX phases were both strongly bonded to the reaction area formed between the two phases. The Ti3SiC2 composites in general had the highest hardness and wear resistance followed by the Ti2AlC composites and last was the Ti3AlC2 composites
A thesis submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, School of Chemical and Metallurgical Engineering, in fulfilment of the requirements for the degree of Doctor of Philosophy, 2021